Gender Differences in Risk and Protective Factors Among Youth With EBD: Findings From the NLTS2. (November 2020) - Novak, Abigail; Poling, Daniel; Muller, Rebecca; Peyton, David
Using data from the National Longitudinal Transition Study 2 (NLTS2), we examined risk and protective factors associated with post-secondary outcomes among youth with emotional and behavioral disorders (EBD). Results indicate that, compared to their male peers, females with EBD demonstrated higher levels of social and behavioral skills and higher grades. We also discovered discrepancies between teacher reports and female students' self-reports of academic, social, and behavioral competencies, suggesting females with EBD underestimate their own skills or that teachers are not fully aware of these students' areas of difficulty. We discuss implications of these results related to existing prevention and intervention strategies for females with EBD.